Development of Website Learning Media (Mobirise) Based on Guided Discovery Learning on High School Chemistry Subjects - Supatmi Wulandini; Setia Rahmawan (Jurnal Paedagogy, 2024)
This study aims to develop website learning media (mobirise) based on guided discovery learning on high school chemistry subjects to increase students' understanding and interest in learning buffer solution material. This study used the research and development method with the ADDIE model, which includes five research stages: design, development, implementation, and evaluation. The data collection techniques in this study were interviews, validation sheets, and student response questionnaires. The data obtained were then analyzed qualitatively and quantitatively. The result showed that validation results by material experts and media experts with a percentage of 100% with category very valid. The results of the assessment of the three reviewers received an average score of 89.4, an ideal level of 89.4%, with a very good category. The results of 30 students' responses showed an average score of 92.3 and an ideal percentage of 92.3% with a very good category, so learning media based on guided discovery learning can be feasible for learning.